Farming along desire lines: Collective action and food systems adaptation to climate change. Issue 2 (3rd March 2020) - Soubry, Bernard; Sherren, Kate; Thornton, Thomas F.
Abstract: We examine collective action in the food system of the Canadian Maritimes to determine its effect on the resilience and adaptive capacity of food producers, distributors, retailers and governance institutions. Our data suggest that beyond their immediate benefits for their participants, expressions of collective action generate higher‐level impacts which often translate into drivers of adaptive capacity. Drawing on a metaphor from urban design, we suggest that collective action should be considered a desire line for food systems adaptation: rather than building adaptation strategies based on top‐down design, collective action emerges from farmers' needs and capacities to build financial resilience, enhance human and social capital and strengthen institutional agency within the system. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Résumé: Nous examinons l'action collective dans le système alimentaire des provinces maritimes du Canada afin de déterminer son effet sur la résilience et la capacité adaptive des producteurs agricoles, des distributeurs, des vendeurs, et des institutions gouvernementales. Les données collectées suggèrent que, mis à part ses bénéfices immédiats pour les participants, l'action collective génère des impacts secondaires qui se traduisent souvent en éléments conducteurs pour la capacité adaptive. Inspirés par le design urbain, nous suggérons donc que l'action collective peut agir comme ligne du désir pour l'adaptation des systèmes alimentaires. Plutôt que de bâtir des stratégies d'adaptation descendantes, l'action collective émerge des besoins des agriculteurs ainsi que de leurs capacités à établir la résilience financière, améliorer le capital humain et social, et renforcer leurs capacités d'action et de décision parmi les institutions existantes. A free Plain Language Summary can be found within the Supporting Information of this article.